40.3k views
2 votes
Which expression is equivalent to (StartFraction x Superscript negative 6 Baseline Over x squared EndFraction) cubed? StartFraction 1 Over x EndFraction StartFraction 1 Over x Superscript 5 Baseline EndFraction StartFraction 1 Over x Superscript 9 Baseline EndFraction StartFraction 1 Over x Superscript 24 Baseline EndFraction

User Rds
by
5.7k points

2 Answers

5 votes

Answer:

D on edge 2020 1/x24

Explanation:

User Bowofola
by
5.1k points
4 votes

Answer:


((x^(-6))/(x^2))^3 = (1)/(x^(24))

Explanation:

Given


((x^(-6))/(x^2))^3

Required

Determine the equivalent expression


((x^(-6))/(x^2))^3

First, we need to evaluate the expression in the bracket:

Apply the following law of indices:


(x^a)/(x^b) = x^(a-b)

So:


((x^(-6))/(x^2))^3 becomes

=
(x^(-6-2))^3

=
(x^(-8))^3

Open the bracket

=
x^(-8*3)

=
x^(-24)

Convert the above expression to fraction

=
(1)/(x^(24))

Hence:


((x^(-6))/(x^2))^3 = (1)/(x^(24))

User Exc
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.